Advances and Challenges in Pharmaceutical Therapies to Prevent and Repair Cochlear Injuries From Noise - Bielefeld, Eric C.; Kobel, Megan J. (Frontiers in Cellular Neuroscience, 2019)
Noise induces a broad spectrum of pathological injuries to the cochlea, reflecting both mechanical damage to the delicate architecture of the structures of the organ of Corti and metabolic damage within the organ of Corti and lateral wall tissues. Unlike ototoxic medications, the blood-labyrinth barrier does not offer protection against noise injury. The blood-labyrinth barrier is a target of noise injury, and can be weakened as part of the metabolic pathologies in the cochlea. However, it also offers a potential for therapeutic intervention with oto-protective compounds. Because the blood-labyrinth barrier is weakened by noise, penetration of blood-borne oto-protective compounds could be higher. However, systemic dosing for cochlear protection from noise offers other significant challenges. An alternative option to systemic dosing is local administration to the cochlea through the round window membrane using a variety of drug delivery techniques. The review will discuss noise-induced cochlear pathology, including alterations to the blood-labyrinth barrier, and then transition into discussing approaches for delivery of oto-protective compounds to reduce cochlear injury from noise.